Implementation of the Total Quality Management Model to Support the Work Quality Culture at SMAN 1 Kelumpang Utara - Rusda Rusda; Hasiana Lorenta; Nasri Nasri; Aslamiah Aslamiah; Celia Cinantya (Green Publisher Indonesia, 2025)
The implementation of an effective quality management system is essential in improving the quality of education in high school. This study aims to illustrate the implementation of the Total Quality Management (TQM) model in supporting the work quality culture at SMAN 1 Kelumpang Utara. This study uses a qualitative approach with a case study method. In-depth interviews, participant observations, and documentation were carried out on the principal, 15 teachers, 3 staff, 1 head of sub-division, and 15 students. The data was analyzed using the Miles and Huberman Models, which include data collection, data reduction, data presentation, and verification. The findings show that TQM has been implemented at SMAN 1 Kelumpang Utara with an emphasis on creating consistency of goals, improving the quality of graduates and services, improving the quality and productivity of school stakeholders, leadership in education, eliminating fear and obstacles to success, creating a culture of quality, process improvement, helping students succeed, commitment, and responsibility. However, there are still obstacles in the total involvement of all school members and continuous improvement. A TQM implementation model is necessary to support a quality work culture that involves staff engagement, leadership, partnerships, reward systems, and organizational quality. These components must be based on a system of values, norms, and culture formulated in a vision, mission, and goals that are understood by all members of the organization.